Treatment of palmoplantar hyperhidrosis - Altman, R... S. (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2002)
Palmoplantar hyperhidrosis, excessive sweating from the palms and soles, is often an embarrassing and disabling condition that afflicts individuals of allages. Diagnosis is usually evident based upon the history and visible signsof sweating. Treatment of this condition has proven to be difficult; however, numerous treatment options are now available. The therapeutic armamentarium includes topical and systemic agents, iontophoresis, botulinum toxin injections, and sympathectomy, all of which will be discussed.
Keywords: Botulinum toksini; Botulinum toxins; Cholinergic antagonists; Drug therapy; Hiperhidroza; Holinergični antagonisti; Hyperhidrosis; Iontoforeza; Iontophoresis; Simpatektomija; Sympathectomy; Therapy